2019
DOI: 10.35219/foodtechnology.2019.1.05
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lactic fermentation on nutritional potential of multigrain flours based on wheat, rye and oat

Abstract: This study was focused on the multigrain flours obtained by milling blends with various amounts of wheat, rye and hulled oat, and on the sourdoughs prepared out of these flours using different commercial starter culture. The folate and total phenol levels and 2,2-diphenyl-1-picrylhydrazyl radical scavenging activity (DPPH-RSA) of multigrain flours increased with the addition level of rye and hulled oat. Among the fractions obtained through milling, higher levels of folates were registered in brans, followed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…Samples KAW (100) and PAW (100) were found to have the maximum total phenol content of 0.157 and 0.168 mg GAE/g dry extract, respectively. The results obtained were similar to the outcomes of the study conducted by (Aprodu et al, 2019) wherein various milling blends of the multigrain flour fermented with different commercial starter cultures were analyzed. It was found that there was an increase in folate, total phenol level and 2,2‐diphenyl‐1‐picrylhydrazyl radical scavenging activity (DPPH‐RSA) in the multigrain flour with addition of rye and hulled oat.…”
Section: Resultssupporting
confidence: 85%
“…Samples KAW (100) and PAW (100) were found to have the maximum total phenol content of 0.157 and 0.168 mg GAE/g dry extract, respectively. The results obtained were similar to the outcomes of the study conducted by (Aprodu et al, 2019) wherein various milling blends of the multigrain flour fermented with different commercial starter cultures were analyzed. It was found that there was an increase in folate, total phenol level and 2,2‐diphenyl‐1‐picrylhydrazyl radical scavenging activity (DPPH‐RSA) in the multigrain flour with addition of rye and hulled oat.…”
Section: Resultssupporting
confidence: 85%
“…This hypothesis is in agreement with prior works ( Nyström et al., 2008 ) and should be considered of great interest, as the non-bound fraction of phenolic acids is believed to be readily available for absorption in the small and large intestines of humans ( Manach et al., 2004 ) and it has been indicated to be the most flavor-active, thereby contributing to the perceived flavor of rye products ( Heiniö et al., 2008 ). Aprodu and Banu (2016) , by means of the DPPH (2,2-diphenyl-1-picrylhydrazyl-hydrate) free radical scavenging method, observed a higher AC for rye than for wheat and triticale samples (1.4 and 1.3-times higher, respectively), while Michalska et al. (2007) , who compared whole-grain rye breads with commercial wheat rolls, reported superior antioxidant properties for the rye baked samples.…”
Section: Discussionmentioning
confidence: 99%
“…Trbović et al (2013) showed that feed influence the proximate composition of carp during rearing. Aprodu et al (2012) showed that carp fed with a diet with fish oil, compared with those fed with a control feed or a feed with the addition of olive or soybean oils, had less protein, more fat and lower energy value (kcal/100 g) of the meat. In contrast, Borowiec et al (2010) showed that the mixture of sunflower and rapeseed oils had no effect in the content of basic nutrients of meat between the experimental and control carp groups.…”
Section: Discussionmentioning
confidence: 99%